2018
DOI: 10.1007/s10029-018-1739-7
|View full text |Cite
|
Sign up to set email alerts
|

Complications and recurrence rates of patients with Ehlers-Danlos syndrome undergoing ventral hernioplasty: a case series

Abstract: PurposeVentral hernia repair is one of the most frequently performed surgical procedures, though recurrences are common. Recurrence can be caused by impaired collagen formation or maturation; hence, patients with Ehlers-Danlos syndrome (EDS) are potentially at increased risk for hernia recurrence. EDS causes altered collagen metabolism, though little is known about the influence of EDS on ventral hernioplasty outcomes. This study aims to analyze these patients to report complication rates, recurrence rates, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In high-risk patients, the incidence increases to up to 30% [5,6]. The identified patient-related risk factors are obesity (BMI > 25 kg/m 2 ), the presence of an abdominal aortic aneurysm and congenital connective tissue disorders [7][8][9][10][11][12]. Furthermore, postoperative wound complications are an independent risk factor for the development of an incisional hernia [9].…”
Section: Introductionmentioning
confidence: 99%
“…In high-risk patients, the incidence increases to up to 30% [5,6]. The identified patient-related risk factors are obesity (BMI > 25 kg/m 2 ), the presence of an abdominal aortic aneurysm and congenital connective tissue disorders [7][8][9][10][11][12]. Furthermore, postoperative wound complications are an independent risk factor for the development of an incisional hernia [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we demonstrated that greater mesh width was associated with lower recurrence rates. This may be attributed to increased coverage and support of the hernia defect, enhanced tissue ingrowth and incorporation, and improved tension distribution across the abdominal wall . Limited studies have analyzed effects of mesh overlap as well as mesh area-to-defect ratio on recurrence; however, few if any have specifically examined the impact of exact mesh size on recurrence rates.…”
Section: Discussionmentioning
confidence: 99%